PENINGKATAN EFISIENSI DAN PRODUKTIVITAS KERJA PADA PRODUKSI KERAJINAN PERAK (Studi kasus : Salim Silver Kota Gede) - , RISA DEWI PUSPITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Productivity and efficiency are the most important things in a production process. The best production process is if the output of production same as required before. To improve the efficiency and productivity of a production line in a manufacturing process, there needs to balance the workload at each workstation. The unbalanced workload between the work stations with other work stations it is showed by a unit of output produced in a same time but has a significant different output. So that it caused a buildup of material on a particular work station and it causes a delay in the production process of the target. The study begins with the observation of the entire production process and attention to production for processing time for each work station. Looking for the work station which have the higher and the lowest productivity. After have the results which is get the station that have the lowest productivity, the research would be analyze spesifiacly on that work station. After that, calculating the standard time to determine the level of efficiency and productivity of the work station, and made observations on each production process at this work station. The results of this research work staisun which have a lowest productivity is at cutting plate design work station. time production process at the work station is still not able to say efficient because they can not meet the needs of production that do some alternative solutions that the design can be used for several types of design and manufacture of cutting tools at the same time with the new design. So after calculation and comparison before and after repair with the use of a new design production time reduced by 22.2%, but with the improvement of production time can not meet the needs of production in accordance with the desired time so that the repair is done the second alternative is the use of cutting tools time turns on the cutting process was reduced by 48% from the start of production time before the repair. Repair time the production process also led to the production activity can be increased up to 25%.